Chillax Cafe / Setila Anthony ... [et. al] - Anthony, Setila; Andan, Dora Jelening; Jelum, Lucynani; Andom, Julina Atun; Richarson, Amelia (2017)
Our business is owned actively by partnership. As a small startup company, we recognize the limitation of attempting to manufacture our products in a small premise. So that, our companies can more concentrate on making the products, as well as give good services to produce our products based on our customer demand. Besides that, our business is locates at New Township, Mukah. We choose this location because it is situated in the center area of people passage from every place in New Township which it nearby of popular shopping complex Medan Mall. Our business is based on providing food and beverage. We choose this business because it's make high profit and can expand future expectation. Besides that, it can attract potential customer to buy it